PENGARUH PENGGUNAAN WEBSITE BOGORKAB.GO.ID DENGAN SISTEM ONE ROOF SERVICE TERHADAP KEPUASAN PELAYANAN PUBLIK KABUPATEN BOGOR - Muhammad Ilham Dewantara (2022)
Generally, public service activities are carried out face to face or directly without using intermediaries. However, along with the rapid development of the internet, many people are starting to recognize and use digital media such as websites. This makes various public service agencies begin to take advantage of the era of digital media development to be able to provide the best digital-based services. One of them is the Bogor Regency Government which uses the website as a public service medium. Over the last few months website Bogorkab.go.id website of Bogor Regency, has experienced a very drastic increase in users. Based on the phenomenon that occurs, the researcher wants to know how much influence the use of website has on increasing satisfaction with public services in Bogor Regency. A total of 100 respondents became the object of research, namely the Bogor community who used website Bogorkab.go.id. The Diffusion of Innovation Theory is used as the main basis for the research assumptions. The method used in this research is quantitative with the type of explanatory research, and the survey was chosen as the method for collecting data. The results of the validity test found r count > r table so that all statements in this study are valid. The conclusion of this study is that there is an influence between the use of website on increasing satisfaction with public services in Bogor Regency.